THE BIRDS OF PALEMBANG PUNTI KAYU RECREATION FOREST, SOUTH SUMATRA, INDONESIA - Iqbal, Muhammad; Setiawan, Doni; Prasetyo, Catur Yuono (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
The Punti Kayu Recreation Forest is artificial pine forest designated as â€œlungsâ€ andÂ park in Palembang City. The birds recorded in Punti Kayu were reviewed to looking at the importance of the forest for natural habitat of birds. A total of 44 species from 24 families of bird was recorded here. This critical reviewed is constitutes first compilation made ever for birds Punti Kayu Recreation Forest.Keywords: Checklist, birds, Punti Kayu, pine forest, South Sumatra.